Reduction of water calcium hardness in the denitrifying biofilter - Ivan Borysov; Ihor Kovalenko; Viktor Gevod; Liliya Frolova (Green Chemistry Letters and Reviews)
Sustainable development goals emphasize the need for cost-effective removal of nitrates from water of sources where there is no centralized tap water supply. This paper describes the properties of the carbonate system in the filtrate of the point of use handy submersible denitrifying biofilter. Device has a U-shaped design with open tops of both elbows and operates in displacement (piston) mode. These allows getting up to 5 liters of denitrified water daily in one gulp, reducing the concentration of nitrate ions in the water by 96-98% from its initial value of [Formula: see text] and the water hardness to reduce depending of initial nitrate concentration. The denitrification process occurs with the consumption of ethyl alcohol as a bacterial food substrate injected to water and accompanies by the accumulation of alkaline bacterial exometabolites in the filtrate. During the microbiological transformation of [Formula: see text] nitrate ions into nitrogen gas, the filtrate enriches with [Formula: see text] bicarbonate ions and [Formula: see text] of hydroxyl ions. This results in a reduction of filtrate hardness from 3.75 mg-eq/L to 1.87 mg-eq/L when in contact with atmospheric air. Physical experiments and mathematical modeling verified the concentrations of carbonate components and calcium ions in both the initial and denitrified water.